MANAJEMEN KEPALA SEKOLAH DALAM PENGEMBANGAN KEGIATAN EKSTRAKURIKULER UNTUK MENDUKUNG PRESTASI SENI DI SDN BAUJENG II KECAMATAN BEJI - Ceria Azizah; Suyanto; M. Furqon Wahyudi (STKIP Subang, 2025)
This study aims to describe the principal's management in developing extracurricular activities to support art achievements at SDN Baujeng II, Beji District. This research uses a qualitative approach with a case study design. Data were collected through interviews, observation, and documentation. The results show that the principal's management involves structured planning through talent mapping, organizing competent art mentors, and intensive supervision ahead of the FLS2N competition. This management significantly contributes to achieving achievements, including winning 3rd place at the provincial level in Storytelling Drawing in 2024. The supporting factor is the high commitment of the school, while the inhibiting factor is the limited infrastructure which is overcome through external collaboration.